Learning Model for Practicing Counting Through the "Snake and Ladders" Game Method - Aenuri Aenuri; Wahyuningsih Wahyuningsih; Aminah Zahro (Journal of Multimedia Trend and Technology, 2023)
The discussion of this paper aims to design and build educational games to train children's numeracy skills in the process of addition and subtraction. Problems occur when children have difficulty understanding, especially in numerical logic. In previous research, it was said that learning for special children at pre-primary school age would be better understood if a game was inserted. Learning to count is the basis for children to have numerical abilities. The method used in making this educational game is Classic Waterfall. With several stages, the results include the use of these games are early childhood. The system development stage includes a Concept that shows the steps of the game here the author makes a snake and ladder single-player game with 50 boxes, the dice in the game are rolled randomly, then the design uses a navigation structure design with a hierarchical storyboard design model. Then at this stage, the feasibility test through Alpha Test and the beta test has been distributed. This game can be done on an Android smartphone via Bluetooth for data transfer.